The Yield Stability and Adaptability of Bambara Groundnut at Three Locations - Gita Novita Sari; Darmawan Saptadi; Kuswanto Kuswanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Varieties with high yield stability are required to increase the yield. This study examines the strength and adaptability of seven Bambara groundnut lines in three areas. The seven lines used are CCC 1.6, PWBG 6, PWBG 521, SS 342, SS 242, BBL 11, and TVSU 86 as checks. The research sites are Brawijaya University Experimental Station, Farmer field in Madiun and Indonesia Legumes, and Tuber Crop Research Institute (ILETRI) Research Station. Research is conducted from February to October 2020. The study used a randomized block design with three replications. The Eberhart-Russel and FinlayWilkinson methods were used to analyze stability and adaptability. The Genotype x Environmental interaction (GxE) results of the 7 Bambara groundnut lines are at 50% flowering time, seed weight per plant, 100-seed weight, yield, and harvest age. The stability and adaptability analysis shows that BBL 1.1 line is the variety with an earlier harvest period, highest yield potential, good stability, and wide adaptability. The CCC 1.1, PWBG 6, PWBG 5.2.1, and SS 2.4.2 production lines are stable in all experimental environments but low productivity. The SS 3.4.2 is suitable for planting in a production environment. TVSU 86 is ideal for producing in marginal habitats such as drought conditions.Â